Development and validation of a questionnaire assessing pharmacists' knowledge and practice towards antimicrobial stewardship in oncology care. - Ali Haider Mohammed; Bassam Abdul Rasool Hassan; Lim Jie Sern; Lim Jing Xuan; Leong Jia Yun; Lim Jing En; Dinesh Sangarran Ramachandram; Angelina Lim; Juman Abdulelah Dujaili; Ali Qais Blebil (PLoS ONE)
Background Cancer patients who receive immunosuppressive therapy are vulnerable to infections due to their compromised immune systems. Therefore, research in promoting the prudent use of antibiotics in this population is essential to optimise patient outcomes and reduce resistance development. The purpose of this study is to develop and validate the Knowledge and Practice of Antimicrobial Stewardship in the Oncology Care Questionnaire (KP-AMS-OC-Q). Method This research is performed in 2 phases. Phase I includes the questionnaire development, item generation, content validity and pilot testing. Phase II encompasses the dissemination of questionnaires to hospital pharmacists and the psychometric evaluation of the validation and reliability of KP-AMS-OC-Q. Specifically, IRT is used to evaluate the knowledge domains, EFA for the practice domains, and Cronbach alpha to measure reliability. Result The finalised version of the questionnaire consisted of 112 items, including 7 social demographics, 49 knowledge, and 56 practice items. IRT conducted has revealed an acceptable difficulty parameter (-3 to +3) in the knowledge domain. Furthermore, EFA has shown a strong internal association between the items and factors, with each item reaching the minimum acceptable factor loading value (>0.3). Besides this, the internal consistency of this questionnaire is favourable, indicated by the Cronbach alpha coefficient of 0.899. Conclusion The results of this study have validated that KP-AMS-OC-Q possesses exceptional psychometric qualities, making it appropriate to measure pharmacists' knowledge and practice towards antimicrobial stewardship (AMS) in oncology care.